The Potential of Microwave Heating in Separating Water-in-Oil (w/o) Emulsions - Nour, A. H.; R. M., Yunus; Azhari, H. Nour; Said, N.; Zulkafli, Hassan (Elsevier Ltd, 2017)
With the increasing energy crisis and the drive to reduce CO2 emissions, the mechanism of microwave heating is essentially that of dielectric heating. In this study, microwave demulsification method was investigated in a 50-50% and 20-80% water-in-oil emulsions with microwave exposure time varied from 20 seconds to 180 seconds. Transient temperature profiles of water-in-oil emulsions inside a cylindrical container were measured. The temperature rise at a given location was almost horizontal (linear). The rate of temperature increase of emulsions decreased at higher temperature due to decreasing dielectric loss of water. Results of this work shown that microwave radiation is a dielectric heating technique with the unique characteristic of penetration, fast, volumetric, and selective heating is appropriate and has the potential to be used as an alternative way in the demulsification process. Microwave demulsification of water-in-oil emulsions does not require chemical additions.